Progress of arylacetamide deacetylase research in metabolic diseases - Yang, Liu; Liao, Zhe-Zhen; Ran, Li; Xiao, Xin-Hua (Frontiers in Oncology, 2025)
Arylacetamide deacetylase (AADAC), a microsomal serine esterase belonging to the polygenic hydrolase family, is predominantly localized in the liver and intestine. It plays a significant role in drug metabolism, lipid metabolism, and the pathogenesis of various diseases. In the context of drug metabolism, AADAC is vital for ensuring the safety of ester-based drugs. Its substrate specificity for short-chain acyl groups, along with genetic polymorphisms among individuals and species, influences drug-related processes. Regarding lipid metabolism, The lipase activity of AADAC is involved in the hydrolysis of cholesterol and triglycerides, lipid mobilization, and the assembly of lipoproteins. The expression of AADAC is regulated by multiple factors. It is associated with metabolic disorders; for instance, its decreased expression in the liver during obesity may impact triglyceride metabolism, and it may also have an indirect role in diabetes. In cardiovascular diseases, AADAC holds potential as a diagnostic marker. Its role in cancer is heterogeneous, being downregulated in certain cancers while upregulated in others, such as pancreatic and ovarian cancers, where it acts to inhibit cancer progression. Within the nervous system, AADAC may influence neurotransmitter regulation and drug metabolism. Currently, research on AADAC agonists is limited, and the development of inhibitors presents challenges, underscoring the necessity for further investigation in this area.